Construction and remote demonstration of an inexpensive but efficient linear differential variable transformer (LVDT) for physics or electronics teaching during COVID-19 pandemic. (1st January 2023) - Roy, Arijit; Roy, Durjoy; Mallick, Abhishek
Abstract: A linear variable differential transformer is termed as LVDT in short. A simple miniature and inexpensive LVDT was constructed for laboratory teaching. Starting from the fundamental physics of LVDT, a complete demonstration was presented. The heart of an LVDT is three coils that were taken from the electrical 'Ding-dong' doorbell. A universal laboratory experiment kit named 'ExpEyes-17' is used to drive the LVDT and display the input and output signals on a laptop screen. Thus, a compact LVDT system was developed. Displacement experiments were conducted, and the well-known V-shape response for our LVDT was obtained. The theory and experiment were presented with a high degree of clarity for ease of understanding. A complete demonstration was given to a group of students while teaching the theory of LVDT, and an excellent response from the group was obtained. Moreover, online demonstration of LVDT experiments using our kit was easily achievable. The authors have used the setup for remote demonstration the experiment to the students during COVID-19 pandemic lockdown.